The correspondence of Just Qvigstad, 1.0 and 2.0 – the ongoing story of a digital edition - Eide, Øyvind; Aspaas, Per Pippin; Conzett, Philipp (Septentrio Conference Series, 2019)
Presentation given at UiT Digital Humanities Conference 2017